2003
DOI: 10.1093/bja/aeg017
|View full text |Cite
|
Sign up to set email alerts
|

Progressive changes in arterial oxygenation during one-lung anaesthesia are related to the response to compression of the non-dependent lung

Abstract: Oxygenation can improve during one-lung ventilation in some patients. This improvement is partly related to a marked increase in Pa(O(2)) during compression of the non-dependent lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 36 publications
0
20
2
Order By: Relevance
“…Although we advocated that compression of the nondependent lung during OLV may be a potentially useful measure to treat hypoxemia in our previous study [11], the present study shows that oxygenation seems to improve with non-dependent lung compression at the expense of CO. Although the mechanisms behind the decrease in CO that accompanies non-dependent lung compression are unclear, there are three possible explanations.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Although we advocated that compression of the nondependent lung during OLV may be a potentially useful measure to treat hypoxemia in our previous study [11], the present study shows that oxygenation seems to improve with non-dependent lung compression at the expense of CO. Although the mechanisms behind the decrease in CO that accompanies non-dependent lung compression are unclear, there are three possible explanations.…”
Section: Discussioncontrasting
confidence: 58%
“…The effects of the release of the lung retractor on hemodynamic parameters and arterial oxygenation were negligible in the present study. However, it should be noted that arterial oxygenation may be impaired after the release of the retractor, since our previous study showed that there was a mild drop in Pao 2 (approximately 43 mmHg on average) in 2 min after decompression of the non-dependent lung by using continuous intra-arterial blood gas monitoring [11]. Since oxygenation is affected by several factors during OLV, such as the time course of hypoxic pulmonary vasoconstriction [14], CO [15][16][17], and epidural anesthesia [18], it is very difficult to analyze the effects of the non-dependent lung compression on the gradual improvement in arterial oxygenation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Certain surgical manoeuvres can be compared with lung compression which can improve oxygenation. 23 Our interpretation is that many factors are involved during the study period and that one can hide another (e.g. time).…”
Section: Discussionmentioning
confidence: 89%
“…The ventilation of only a single lung may be associated with lifethreatening gas exchange impairment [41,42]. In fact, OLV may be associated with a decrease of arterial oxygen saturation below 90 % in *10 % of patients [43,44]. Hypoxemia during thoracic surgery is not mainly caused by a reduced alveolar surface but much more by venous admixture resulting from residual perfusion of the nonventilated lung and from atelectasis and poorly aerated regions in the ventilated lung.…”
Section: One-lung Ventilation (Olv)mentioning
confidence: 99%